Effect of Variability on Cronbach Alpha Reliability in Research Practice - Muhammad Amirrudin; Khoirunnisa Nasution; Supahar Supahar (Jurnal Matematika, Statistika dan Komputasi, 2021)
This study aims to describe the effects of variability through data simulation to determine which aspect of variability that maximizes coefficient of Cronbach Alpha reliability. Cronbach Alpha is widely used for estimation of reliability, in recent still. This study served a conceptual and practical simulation for estimating the profound aspect of Cronbach Alpha coefficient relating to the variability of the data. This study carried out with data simulated using the rand between method by Microsoft Excel then simulate different categorical data responses to different range of items by manipulating sample size, range, number of items, variance and standard deviation. The results show that number of variance and standard deviation of data had the most profound aspect of Cronbach Alpha's reliability other than range. The increasing number on some aspect shows that standard deviation and variance has the stability to shows the positive correlation with the coefficient of Cronbach Alpha reliability other than range.